H.G. Wells: New Objectivity & The Marxist Machine - Almahdi, Nawaf (2019)
This essay was written as my final research paper for Literary Theory & Criticism class (ENG415), a capstone course taught by Professor Malek Hardan Mohammed. This paper focuses on H.G. Wells’ popular novel The Time Machine where I employed theories from the school of Marxism alongside my analysis of the story, where I have identified Wells’ usage of political and social themes that talks of the corruption of his society during the Victorian Era. What makes this essay unique is how Well’ uses fiction and metaphors to converse with the reader about theories about social reformation and possible outcomes if society did not take action in fixing its economy and bringing balance between social classes.